TIPOGRAFI ARAB PEGON DALAM PRAKTIK BERBAHASA MADURA DI TENGAH DINAMIKA KEBUDAYAAN YANG DIUSUNG HURUF LATIN - Naufan Noordyanto (Institut Seni Indonesia Yogyakarta, 2016)
Arabic pegon script or pegon script is the term of a few Hijaiyah/Arabic letters that is generally modified and used to write in Malay and Javanese. In Madura, East Java, Pegon script is used for the writing in the language of Madura and other languages, such as Java language. Unfortunately, practices of writing with Arabic typography Pegon in everyday life today, especially in the area of Madura, still as though vague, because the practice of typography around the world still dominated by